2011
DOI: 10.1016/j.patcog.2011.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical annotation of medical images

Abstract: In this paper, we describe an approach for the automatic medical annotation task of the 2008 CLEF cross-language image retrieval campaign (ImageCLEF). The data comprise 12076 fully annotated images according to the IRMA code. This work is focused on the process of feature extraction from images and hierarchical multi-label classification. To extract features from the images we used a technique called: local distribution of edges. With this techniques each image was described with 80 variables. The goal of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(74 citation statements)
references
References 25 publications
0
72
0
2
Order By: Relevance
“…For more information, see [10]. According to these experiments and previous research the ensembles of PCTs showed increased performance as compared to a single PCT when applied for hierarchical annotation of medical images [13]. Furthermore, the Bagging and Random Forest methods give similar results and because the Random Forest method is much faster than the Bagging method we submitted only the results for the Random Forest method.…”
Section: Experimental Designmentioning
confidence: 66%
“…For more information, see [10]. According to these experiments and previous research the ensembles of PCTs showed increased performance as compared to a single PCT when applied for hierarchical annotation of medical images [13]. Furthermore, the Bagging and Random Forest methods give similar results and because the Random Forest method is much faster than the Bagging method we submitted only the results for the Random Forest method.…”
Section: Experimental Designmentioning
confidence: 66%
“…This is also motivated by the superiority of the hierarchical classification approach in other fields such as text categorization and protein function prediction [7,23,28], where the features are typically high-level and where the possible states of the observed phenomenon are connected via well-understood hierarchical relationships. Enforcing such a hierarchical prior to the classification of visual content has been shown to be advantageous in some works (e.g., [3,6]), but far less often than in other fields [28]. Particularly in our previous work [11], the results of which are also reported in Sect.…”
Section: Discussionmentioning
confidence: 86%
“…As for classification based on visual features, a hierarchical prior intuitively seems especially appropriate as it reflects the natural way in which humans organize and recognize the objects they see, which is also supported by neurophysiological studies of the visual cortex [2,15,35]. In practice, some results have shown that there is indeed a gain in performance with the hierarchical approach in the visual-based application domain, e.g., for 3D object shape classification [3] and annotation of medical images [6]. A quite active and closely related line of work consists of the supervised construction of class hierarchies from images with multiple tag labels.…”
Section: Introductionmentioning
confidence: 93%
“…Based on the results shown in Table 1, the Bag of Words (BoW) and Support Vector Machines (SVM) [8] are used as main image representation technique and classifier, respectively. In the past years, the BoW was successfully employed in various medical image retrieval and classification tasks [9][10][11][12][13][14][15][16][17]. Among other classifiers, SVMs have shown a better generalization performance in medical domain compared with other classification techniques.…”
Section: Methodsmentioning
confidence: 99%